2014
DOI: 10.1002/jcb.24829
|View full text |Cite
|
Sign up to set email alerts
|

Obatoclax Induces G1/G0‐Phase Arrest via p38/p21waf1/Cip1 Signaling Pathway in Human Esophageal Cancer Cells

Abstract: Pan-Bcl-2 family inhibitor obatoclax has been demonstrated to be effective against various cancers, of which the mechanism of action is not fully understood. In this study, we demonstrate that obatoclax suppressed esophageal cancer cell viability with concomitant G1/G0-phase cell cycle arrest. At the tested concentrations (1/2 IC50 and IC50), obatoclax neither induced PARP cleavage nor increased the Annexin V-positive population, suggesting G1/G0-phase arrest rather than apoptosis accounts for most of the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
1
27
2
Order By: Relevance
“…8C). This was different from a previous study which reported suppression of esophageal cancer cell viability by Obatoclax with concomitant G1/G0-phase cell cycle arrest 41. Furthermore, while the p-ERK level in the Vemurafenib-resistant K1 cells did not change as the concentration of Vemurafenib increased, it decreased significantly in the LY3009120-treated group (Fig.…”
Section: Resultscontrasting
confidence: 93%
“…8C). This was different from a previous study which reported suppression of esophageal cancer cell viability by Obatoclax with concomitant G1/G0-phase cell cycle arrest 41. Furthermore, while the p-ERK level in the Vemurafenib-resistant K1 cells did not change as the concentration of Vemurafenib increased, it decreased significantly in the LY3009120-treated group (Fig.…”
Section: Resultscontrasting
confidence: 93%
“…Although BH3 mimetics are designed to trigger apoptosis, accumulating evidence indicates that their anticancer activity is not limited to the initiation of apoptosis. In addition to their pro-apototic effect, BH3 mimetic agents have been shown to exert anti-proliferative effects by blocking cell cycle progression [31,32] and to induce autophagy in tumor cells, mainly because of the release of Beclin 1 from Bcl-2 and Bcl-xL [20,[33][34][35] . However, the mechanism underlying ABT-263-induced cell cycle arrest and autophagy induction had been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AT-101 blocks cell cycle progression by regulating a variety of proteins that mediate G 1 to S phase transition. Of note, our previous studies have demonstrated that other Bcl-2 inhibitors with different chemical structures from AT-101 exhibited a similar pattern on cell cycle progression as well as apoptosis (18,20). Thus, we propose that G 1 /G 0 phase arrest might not be a unique cellular response to AT-101 but instead a common response to Bcl-2 inhibitors, suggesting a potential link between Bcl-2 family members and cell cycle progression.…”
Section: Discussionmentioning
confidence: 65%
“…There is accumulating evidence showing that the antitumor activity of Bcl-2 inhibitors is not limited to the initiation of apoptosis, despite the fact that Bcl-2 inhibitors were originally designed to induce apoptosis. In this regard, Bcl-2 inhibitors have been reported to block cell cycle progression (18,19), regulate autophagy (20)(21)(22) and inhibit tumor stemness (23). It has been showed that AT-101 significantly suppressed the hedgehog (Hh) signaling pathway and suppressed the growth of Hh-driven cancer in vitro and in vivo (24).…”
Section: Discussionmentioning
confidence: 99%